Chemistry of Lipid A: At the Heart of Innate Immunity. Issue 2 (29th October 2014) - Molinaro, Antonio; Holst, Otto; Di Lorenzo, Flaviana; Callaghan, Maire; Nurisso, Alessandra; D'Errico, Gerardino; Zamyatina, Alla; Peri, Francesco; Berisio, Rita; Jerala, Roman; Jiménez‐Barbero, Jesús; Silipo, Alba; et al.
Abstract In many Gram‐negative bacteria, lipopolysaccharide (LPS) and its lipid A moiety are pivotal for bacterial survival. Depending on its structure, lipid A carries the toxic properties of the LPS and acts as a potent elicitor of the host innate immune system via the Toll‐like receptor 4/myeloid differentiation factor 2 (TLR4/MD‐2) receptor complex. It often causes a wide variety of biological effects ranging from a remarkable enhancement of the resistance to the infection to an uncontrolled and massive immune response resulting in sepsis and septic shock. Since the bioactivity of lipid A is strongly influenced by its primary structure, a broad range of chemical syntheses of lipid A derivatives have made an enormous contribution to the characterization of lipid A bioactivity, providing novel pharmacological targets for the development of new biomedical therapies. Here, we describe and discuss the chemical aspects regarding lipid A and its role in innate immunity, from the (bio)synthesis, isolation and characterization to the molecular recognition at the atomic level.